Tubuh Perempuan Dalam Layar Kaca: Perebutan Kuasa Terhadap Tubuh Perempuan Antara Negara, Media dan Pemiliknya - Nurmadiansyah, Thoriq (Sunan Kalijaga State Islamic University & The Asia Foundation, 2007)
This article highlights how the media, especially television, have per, ceived women's bodies. TV has proven itself to be a powerful medium to develop public opinion, including that with regard to women's bodies. TV has propagates many different types of women's bodies: beautiful women, ugly women, nice women with all their characteristics. The State is also interested in controlling women's bodies. This can be seen from the conceptualization of legal draft on pornography that targeted women. Thus media and the state have competed to rule women's bodies as though they are commodity object, whereas women themselves, the right owners of the bodies, are usually left behind in this discourse. The author suggests that women's voice should be listened and considered seriously in this matter, because women are the owners of their bodies.